Melting and Crystallization of Silicate Systems Relevant to Thermal Barrier Coating Damage1. Issue 5 (28th January 2015) - Zaleski, Elisa M.; Ensslen, Charlotte; Levi, Carlos G.
Abstract : The melting and crystallization behaviors of model calcium–magnesium–alumino‐silicate (CMAS) compositions relevant to the degradation of thermal barrier coatings (TBCs) were investigated. A primary goal was to establish a baseline for studies on CMAS reactions with TBC materials, reported separately, and their potential to mitigate degradation. Ternary calcium alumino‐silicate (CAS) compositions investigated melt below their equilibrium solidus owing to their metastable phase constitution. Additions of MgO or FeO x have significant effects on the melting behavior, depending on the C:A:S proportions. Amorphization on cooling is commonplace, with MgO, AlO1.5, and especially FeO x promoting crystallization. The behaviors of amorphous and crystalline versions of the same CMAS are different and depend on heating/cooling rates, with attendant implications for their interaction with TBCs.